ChemInform Abstract: Catalytic Enantioselective Silylation of N‐Sulfonylimines: Asymmetric Synthesis of α‐Amino Acids from CO2 via Stereospecific Carboxylation of α‐Amino Silanes. Issue 48 (2nd December 2014) - Mita, Tsuyoshi; Sugawara, Masumi; Saito, Keisuke; Sato, Yoshihiro
Abstract An asymmetric silylation of N‐tert‐butylsulfonylimines by using a Cu‐secondary diamine complex as the catalyst is developed.